Evaluation of underutilised plants and agro-industrial by-products as potential substrates for rearing black soldier fly larvae, Hermetia illucens (Diptera: Stratiomyidae) for inclusion in Asian seabass (Lates calcarifer) diets - Wan Md Zain, Wan Somarny (2023)
The current model, which uses fish meal (FM) as the primary source of protein for fish, cannot be maintained indefinitely. As a result, there is a need for further research into alternative sources that are both high in protein and fat. The larvae of the black soldier fly (BSFL, Hermetia illucens) have attracted research attention due to their nutritional values and ability to be reared on a wide variety of organic waste. This study aims to assess the potential of BSFL meal (BSFLM) as a substitute for FM in the diet of Asian seabass (Lates calcarifer). Two underutilised plant species, Moringa oleifera (MO) and Sesbania grandiflora (SG), and four agro-industrial by-products (AIBPs), including soybean waste (SBW), wheat pollard (WP), rice bran (RB), and milk-extracted coconut meat (MECM), either single or in combination (MECM:SG), were evaluated as feed substrates for rearing BSFL. Different substrates significantly affected (p < 0.05) the final weight, size, larval development time, and nutrient composition of BSFL. Larvae fed with RB had the highest weight gain, with high concentrations of protein and fat (50.8 and 31.8 g/100g DM, respectively). The highest wet weights of larval biomass (659 – 682 g) were achieved on high protein substrates (MO, SG, and SBW). Larvae reared on AIBP had higher levels of essential amino acids (around 27 g/100g DM) than those reared on leaf-meals (around 23.5 g/100g DM), particularly WP- and RB-fed larvae. Meanwhile, larvae had a high content of saturated fatty acids (SFA), ranging from 54 to 93% of total FA. Larvae fed WP and RB had the highest levels of polyunsaturated fatty acids of about 26% of total FA. In the present study, based on the optimal nutrient composition and growth performance of the larvae, day 17 was selected as the best time for harvesting BSFL for all single feed substrates. On the mixed feed substrates (MECM:SG), the crude protein (CP) and fat of larvae increased with the increase of SG and MECM, respectively, ranging from 33.5 – 54.3 g/100g DM and 12.9 – 33.8 g/100g DM. The optimum day to harvest the mixed substrate-fed larvae was on day 19, due to the larval wet weight, higher larval CP content, and the best conversion of feed substrate into larval biomass (23%), particularly for the BSFL fed on the 1:1 ratio of MECM:SG substrate. The BSFL on this mixed substrate was further evaluated for its potential to replace FM in the diet of Asian seabass.